Estimation of Hepcidin Role and some Biochemical Parameters in Patients with Beta- thalassemia in Thi-Qar Governorate/ Iraq - Majid, Alyaa; Alyar , Saliha; Almusawi, Mohammed Yasir (University of Thi-Qar Journal of Science, 2024)
The β-thalassemias are a group of recessively inherited genetic disorders that cause varying amounts of hemoglobin production. The study's aim was to look at hepcidin, ferretin, iron, PCV, Hb, ALT, AST, and albumin levels. Serum hepcidin, ferretin, iron, PCV, Hb, ALT, AST, and albumin levels were determined in 55 patients with beta-thalassemia and 55 healthy individuals. The results demonstrated a substantial rise in serum concentrations of ferretin, iron, ALT and AST in the beta-thalassemia group as compared to the control group(p<0.001). There was also a significant decrease in the concentrations in the serum of hepcidin, packed cell volume, hemoglobin and albumin (p<0.001).